2021
DOI: 10.3390/jcm10235705
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Hemorrhage after SARS-CoV-2 Vaccination

Abstract: To report retinal vein occlusion (RVO) and age-related macular degeneration (AMD)-related submacular hemorrhage developing after administration of SARS-CoV-2 vaccines, a single-center, retrospective observational case series was conducted. Clinical data including fundus photographs and optical coherence tomography (OCT) scans were reviewed. Twenty-three eyes of 21 patients were included with the median age at symptom presentation being 77 years (range: 51–85 years). Twelve eyes (52.2%) had submacular hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Endo et al [ 24 ] reported the case of a 52-year-old man who developed BRVO 15 days after receiving SARS-CoV-2 vaccination, knowing that no recent condition related to developing RVO was present. In a similar case series study, Park et al [ 14 ] also reported 11 cases of subretinal hemorrhage and RVO after receiving SARS-CoV-2 vaccination. This report suggests that RVO onset after SARS-CoV-2 vaccination could occur with or without a related medical history and across any type of vaccine formulation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Endo et al [ 24 ] reported the case of a 52-year-old man who developed BRVO 15 days after receiving SARS-CoV-2 vaccination, knowing that no recent condition related to developing RVO was present. In a similar case series study, Park et al [ 14 ] also reported 11 cases of subretinal hemorrhage and RVO after receiving SARS-CoV-2 vaccination. This report suggests that RVO onset after SARS-CoV-2 vaccination could occur with or without a related medical history and across any type of vaccine formulation.…”
Section: Discussionmentioning
confidence: 88%
“…[ 4 5 6 7 ] Additional postvaccine adverse events affecting the eyes have also been reported, including keratoplasty rejection,[ 8 9 ] panuveitis,[ 10 ] abducens nerve palsy,[ 11 ] episcleritis,[ 12 ] anterior scleritis,[ 12 ] acute macular neuroretinopathy,[ 12 ] paracentral acute middle maculopathy,[ 12 ] eyelid localized purpuric and ecchymotic reactions,[ 13 ] and subretinal hemorrhage due to age-related macular disease. [ 14 ] Moreover, we reported previously two cases with exacerbation of branch retinal vein occlusion (BRVO), implicating a possible association with SARS-CoV-2 vaccination. [ 15 ] However, the association between SARS-CoV-2 vaccination and the first onset of retinal vascular occlusion disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal vascular adverse events after COVID-19 vaccinations appear to be rare [ 11 ]. However, there is now a growing literature reporting single case reports with RVO after both mRNA vaccines including mRNA-1273 (Moderna) [ 12 ] and BNT162b2 (Pfizer) [ 13 16 ], and vector-based ChAdOx1 (Vaxzevria) [ 17 19 ]. Other single case reports have documented combined CRAO-CRVO shortly after mRNA-1273 (Moderna) [ 20 ], combined CRAO-CRVO with ischemic optic neuropathy after BNT162b2 (Pfizer) [ 21 ], and CRAO after ChAdOx1 (Vaxzevria) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cases with vitreous hemorrhage (cases #6~8) had a history of vitrectomy due to vitreous hemorrhage which accompanied the RVO, meaning that there was previous neovascularization. Park et al reported on submacular hemorrhage and vitreous hemorrhage in a patient with age-related macular degeneration and RVO [ 7 ]. The vessel vulnerable to microvascular dysfunction including neovascularization due to AMD and RVO may develop hemorrhagic complications after COVID-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Serious vaccine-related effects, including thrombotic thrombocytopenia, cerebral venous sinus thrombosis, splanchnic vein thrombosis, and pulmonary embolism, were reported after vaccination for COVID-19 [ 2 , 3 , 4 , 5 , 6 ]. In terms of ophthalmic reaction to COVID-19 vaccination, various manifestations including eyelid swelling, ptosis, superior ophthalmic vein thrombosis, acute graft rejection after keratoplasty, cranial nerve palsy, retinal vein occlusion, submacular hemorrhage, scleritis, uveitis, acute macular neuroretinopathy, optic neuritis, and paracentral acute middle maculopathy were found in several cases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The COVID-19 vaccines with reported ophthalmic reactions included the mRNA vaccine (BNT162b2, Pfizer, Brooklyn, NY, USA; mRNA-1273, Moderna, Cambridge, MA, USA), vector vaccine (Ad26COVS1, Janssen Johnson & Johnson, New Brunswick, NJ, USA; AZD1222, Oxford–AstraZeneca, Cambridge, UK), and whole virus (PiCoVacc, Sinovac Biotech, Beijing, China; BBIBP-CorV, Sinopharm, Beijing, China) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%